Radical orthodoxy : a new theology - Milbank, John; Pickstock, Catherine; Ward, Graham (Routledge Radical Orthodoxy., 1999)
Radical Orthodoxy is a new wave of theological thinking that aims to reclaim the world by situating its concerns and activities within a theological framework, re-injecting modernity with theology. This collection of papers is essential reading for anyone eager to understand religion, theology, and philosophy in a completely new light.